Pengaruh Model Pembelajaran Group Investigation terhadap Hasil Belajar PKn Siswa Kelas V Sekolah Dasar - Rizzaludin, Rizzaludin; Hidayat, Hidayat; Idhar, Idhar; Srirahmawati, Ija; Yusnarti, Mulya (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2024)
The Group Investigation (GI) Learning Model is a learning model where the teacher only acts as a motivator and facilitator and provides opportunities for participants to participate more actively in managing information, thinking critically and being responsible. This learning model allows students to find for themselves the information needed to achieve indicator goals and learning objectives. This research aims to determine the influence of the Group Investigation (GI) learning model on PKN Class V learning outcomes at SDN 07 Manggelewa in 2019/2020. This type of research is quasi-experimental with a quantitative approach. The population is all class V students, totaling 22 students. The sample used was 11 VA class students as the experimental class, 11 people as the control class. The sampling technique uses a purposive sample. Data was obtained through pretest and posttest and then analyzed using the t-test. Based on the initial test, the experimental class average was 51 and the control class was 47. The final test results showed the experimental class average was 77 and the control class was 74. The sample class final test data was analyzed using the t-test. The t-test results obtained tcount of 3.108 and ttable of 1.724. It was obtained that tcount was greater than ttable at an error level of 5%. Based on the hypothesis obtained, there is an influence of the Group Investigation (GI) Learning Model on Class V PKN Learning Outcomes at SDN 07 Manggelewa.